Adoption of Augmented Reality - Potential use-cases in an industry context - Ekelöf, Ida; Hedkvist, Emelie (My University, 2017)
Industries of today experience increased competition and cost pressure, further the trends Industry 4.0 and servitization have emerged. A technology that could facilitate for the necessary business transformation, further support the increased amount of digital content, is Augmented Reality. This report aims to give a comprehensive understanding of what, positively or negatively, influences the adoption of AR amongst asset intensive manufacturers, from an external environment-, organizational-, and a technological perspective. Furthermore, different use-cases for AR have been evaluated in order to determine whether these are applicable today, or rather in the future. The research was of qualitative nature and both primary- and secondary data sources have been used. The primary data were collected from interviews with industry experts, AR experts, and managers or employees involved in AR initiatives. The secondary data were mainly collected from consultancy reports, but also from panel discussions and seminars. It was found that AR is a communication and visualization tool, that has great potential to deliver business value due to its ability to support a mixed reality, in other words the merge of the realand the digital world. Furthermore, by the usage of a head-mounted-display (HMD) device, additional value propositions could be received, such as hands-free. Therefore, it is believed that AR by the usage of HMD brings the highest business potential, further that it will become the next computer platform. However, there are many technical limitations that must be solved in order for AR to achieve its full potential. Furthermore, it was found that the current AR-market is highly fragmented, and there are no standards regarding hardware, platforms, and how to describe information. Similarly, companies are uncertain regarding AR’s capabilities, and the cost and benefits of an AR investment. Therefore, these concern must be solved in order for AR to take off. Ten different use-cases were found valuable for asset intensive manufacturers, and a common theme amongst these were that AR facilitated for increased understanding and collaboration. The focus in a short time-horizon should be on applications that solves a critical problem, as well as providing high business value. Furthermore, the current focus should be on applications with low technical requirements, and where it is possible to reuse existing content. Therefore, the most valuable use-areas from a short time-horizon are: remote guidance, visualization of 3D models, and dashboarding. However, several of the other use-cases will become beneficial in a near future, further new applications will arise in the future.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics